Adult ADHD Positive Screening and Sibship, Birth Order and Academic Achievement: Implications for Epidemiologists and Physicians in the Kingdom of Saudi Arabia - AlOmar RS; AlShamlan NA; Al-Johani WM; Almayyad AH; Alotaibi HK; Alsamin SI; Alfrayyan NY; Boubshait LA; Alghamdi LM; Al-Shammari MA (Psychology Research and Behavior Management, 2023)
Reem S AlOmar,1 Nouf A AlShamlan,1 Wejdan M Al-Johani,1 Ali H Almayyad,1 Hadeel K Alotaibi,1 Sarah I Alsamin,1 Naif Y Alfrayyan,2 Leila A Boubshait,1 Layla M Alghamdi,1 Malak A Al-Shammari1 1Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi Arabia; 2Internal Medicine Department, Psychiatry Division, Security Forces Hospital, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Reem S AlOmar, Email rsomar@iau.edu.saBackground: Attention deficit hyperactivity disorder (ADHD) among the youth and university students differs internationally. This study aims to assess the prevalence of ADHD positivity from a validated screening test among medical students across the Kingdom of Saudi Arabia (KSA) and its associated sociodemographic and family-related factors and the impact of ADHD on students’ academic performance. Also, to highlight the implications of the current findings on epidemiologists and family physicians in the region.Methods: This cross-sectional study utilised the Adult ADHD Self-Report Scale (ASRS) symptom checklist along with several questions on sociodemographic, siblings and personal academic achievement. Multivariable logistic regression models were performed to obtain the Odds Ratios (ORs) of risk of ADHD screening positivity and their 95% confidence intervals (CIs) against potential predictors.Results: The overall prevalence of positively screened medical students was 38.86%. After adjustment, a statistically significant increased risk of ADHD positivity was observed for students who had one sibling (OR = 1.70, 95% CI = 1.09– 2.64). Also, upon examination of birth order, a significant increased risk was observed for students who were firstborn (OR = 1.22, 95% CI = 1.02– 1.47). With regard to academic achievement, both before and after adjustment, students who screened positive had a 14% increased risk of obtaining an F GPA (OR = 1.14, 95% CI = 0.99– 1.30).Conclusion: A considerable number of medical students are potentially positive for ADHD. Albeit not diagnostically confirmed – this indicates that a substantial number of people have displayed symptoms akin to ADHD, but were not clinically diagnosed. Research into ADHD in the region is still in its infancy, and epidemiologists would benefit from high-quality databases to address this condition. Also, primary care physicians should develop skills in detecting and managing ADHD in children at an earlier age to improve symptoms in adulthood.Keywords: attention deficit hyperactivity disorder, epidemiology, family physicians, cross-sectional study, Kingdom of Saudi Arabia